The treatment burden of long-term home noninvasive ventilation. Issue 1 (March 2021) - Spurr, Lydia
The prevalence of long-term home noninvasive ventilation (NIV) has progressively increased over recent decades, supported by evidence of clinical effectiveness in a range of conditions leading to chronic respiratory failure [1, 2]. Simultaneous technological developments have improved the reliability, portability, and comfort of devices, making NIV increasingly accessible and acceptable as a treatment option [3]. Clinicians are usually fully cognisant of the clinical outcomes they anticipate when recommending or initiating long-term NIV, for example prolonging life, preventing complications or healthcare utilisation, and/or improving symptoms. The evidence on key clinical outcomes is variable between conditions but is comprehensively evaluated in relevant clinical guidelines; traditionally less emphasis is placed on the potential practical and psychosocial implications of domiciliary NIV. However, the preferences, values and resources of individuals can have a significant impact on NIV usage and therefore may affect potential clinical benefit. This editorial discusses the healthcare-associated workload, also known as the treatment burden, of domiciliary NIV that may be shouldered by patients, their families and caregivers, justifying why the cost/benefit ratio must be carefully considered on an individual basis. Long-term home noninvasive ventilation has practical and psychosocial implications for individuals, families and caregivers. Exploring the impact of the workload of healthcare or "treatment burden" helps determine treatment feasibility and acceptability. https://bit.ly/39YUY2A